Physical activity as a determinant of fasting and 2‐h post‐challenge glucose: a prospective cohort analysis of the NAVIGATOR trial. Issue 8 (12th April 2015) - Yates, T.; Davies, M. J.; Haffner, S. M.; Schulte, P. J.; Thomas, L.; Huffman, K. M.; Bales, C. W.; Preiss, D.; Califf, R. M.; Holman, R. R.; McMurray, J. J. V.; Bethel, M. A.; et al.
Abstract Aim To investigate whether previous physical activity levels are associated with blood glucose levels in individuals with impaired glucose tolerance in the context of an international pharmaceutical trial. Methods Data were analysed from the NAVIGATOR trial, which involved 9306 individuals with impaired glucose tolerance and high cardiovascular risk from 40 different countries, recruited in the period 2002–2004. Fasting glucose, 2‐h post‐challenge glucose and physical activity (pedometer) were assessed annually. A longitudinal regression analysis was used to determine whether physical activity levels 2 years (t‐2) and 1 year (t‐1) previously were associated with levels of glucose, after adjusting for previous glucose levels and other patient characteristics. Those participants with four consecutive annual measures of glucose and two consecutive measures of physical activity were included in the analysis. Results The analysis included 3964 individuals. Change in physical activity from t‐2 to t‐1 and activity levels at t‐2 were both associated with 2‐h glucose levels after adjustment for previous glucose levels and baseline characteristics; however, the associations were weak: a 100% increase in physical activity was associated with a 0.9% reduction in 2‐h glucose levels. In addition, previous physical activity only explained an additional 0.05% of the variance in 2‐h glucose over the variance explained by the history of 2‐h glucose alone (R2 = 0.3473 vs. 0.3468). There was no association with fasting glucose. Conclusions In the context of a large international clinical trial, previous physical activity levels did not meaningfully influence glucose levels in those with a high risk of chronic disease, after taking into account participants' previous trajectory of glucose control.